Size, Composition, and Support-Doping Effects on Oxygen Reduction Activity of Platinum-Alloy and on Non-platinum Metal-Decorated-Graphene Nanocatalysts - Lozano, Tamara; Rankin, Rees B. (Frontiers in Chemistry, 2019)
ABSTRACT Recent investigations reported in the open literature concerning the functionalization of graphene as a support material for transition metal nanoparticle catalysts have examined isolated systems for their potential Oxygen Reduction Reaction (ORR) activity. In this work we present results which characterize the ability to use functionalized graphene (via dopants B, N) to upshift and downshift the adsorption energy of mono-atomic oxygen, O*, (the ORR activity descriptor on ORR Volcano Plots) for various compositions of 4-atom, 7- atom, and 19-atom sub-nanometer binary alloy/intermetallic transition metal nanoparticle catalysts on graphene (TMNP-MDG). Our results show several important and interesting features: 1) that the combination of geometric and electronic effects makes development of simple linear mixing rules for size/composition difficult; 2) that the transition from 4- to 7- to 19-atom TMNP on MDG has pronounced effects on ORR activity for all compositions; 3) that the use of B and N as dopants to modulate the graphene-TMNP electronic structure interaction can cause shifts in the oxygen adsorption energy of 0.5 eV or more; 4) that it might be possible to make specific doped- graphene-NixCuy TMNP systems which fall close to the Volcano Peak for ORR. Our results point to systems which should be investigated experimentally and may improve the viability of future fuel cell or other ORR applications, and provide new paths for future investigations of more detail for TMNP-MDG screening.